Long-term mucosal recovery and healing in celiac disease is the rule – not the exception. (1st December 2016) - Hære, Petter; Høie, Ole; Schulz, Tom; Schönhardt, Irina; Raki, Melinda; Lundin, Knut E. A.
Abstract: Objective: The prevalence of persistent villous atrophy (VA) in patients with celiac disease (CD) on a gluten-free diet (GFD) varies greatly between studies. Most studies show a relatively high prevalence of mucosal atrophy and inflammation in treated patients, a finding which have led to a concept of non-responsive CD. Few studies have examined the prevalence of long-term mucosal healing. Our study aimed to determine the extent of mucosal healing in a cohort of Norwegian patients with CD treated with GFD for several years. Materials and methods: Adult patients diagnosed with VA between 1989 and 2009 were included. We performed a follow-up gastroscopy with duodenal biopsies. Two pathologists evaluated the biopsies according to the Marsh–Oberhuber classification. Mucosal healing was defined as Marsh 0 while mucosal recovery was defined as Marsh 0-2. Results: Duodenal biopsies were obtained from 127 adult patients with established CD. After a follow-up time of 8.1 years (median, range 2.3–22.3), 103 (81%) of the patients showed mucosal healing, 120 patients (94%) showed mucosal recovery, and 7 patients (6%) showed persistent VA. In addition, 103 of the 127 patients (81%) had undergone a routine follow-up biopsy 12.6 months (median, range 5.2–28.8) after diagnosis. At the time of the routine follow-up, only 52 of these patients (50.5%) had achieved mucosal recovery. Conclusions: Although half of the patients had persistent VA at the time of routine follow-up, both long-term mucosal recovery and healing is possible for the vast majority of adult patients with CD.